Reinforcement of contours in medical images using an adaptive filter - Servin, G. M.; Rodriguez, V. R. (Revista Mexicana de Ingenieria Biomedica, 2018)
It is a well-known fact [1,2] that a Laplacian matrix can be useful for reinforcing high frequencies in an image. However, as shown in this work, the quantization noise in the digitized image becomes very large. In this article we analyze a Laplacian type filter that adapts to the local variance of the image measured in a 3x3 pixel window. This filter can change depending on this local variance, from a low pass filter, which decreases the inherent noise of quantization in regions of quasi constant gray level, to a high pass filter, in highly contrasted regions of the image. The results obtained demonstrate the significant advantages of this adaptive filter.